Understanding large plastic deformation of SiC nanowires at room temperature - Wang, Jun; Lu, Chunsheng; Wang, Q.; Xiao, P.; Ke, F.; Bai, Y.; Shen, Y.; Liao, X.; Gao, H. (Institute of Physics Publishing Ltd., 2011)
Tensile behaviors of SiC [111] nanowires with various possible microstructures have been investigated by molecular-dynamics simulations. The results show that the large plastic deformation in these nanowires is induced by the anti-parallel sliding of 3C grains along an ultra- thin intergranular amorphous film parallel to the (11¯1) plane and inclined at an angle of 19.47◦ with respect to the nanowire axis. The resulting large plastic deformation of SiC nanowires at room temperature is attributed to the stretching, breaking and re-forming of Si–C bonds in the intergranular amorphous film, which is also evident from the sawtooth jumps in the stress-strain response.